IMPLEMENTATION OF HYDROPONIC SENSORS AND MONITORING SYSTEM USING IOT - Meor Mohamad Zamil, Meor Muhammad Faiz (IRC, 2019)
Farming is one of the fundamental inventions that promoted the flourishing or human species on planet earth. Since many centuries have past, this fundamental invention namely the conventional way of it has become reverse which is promoting extinction. Conventional farming has led to many unsustainable acts such as deforestation, heavy use of pesticides and insecticides, feces as fertilizers, open burning and creation of cities. These acts in turn backfired resulting in global warming, extreme climate change (drought, flood, hurricanes etc), exponential rise in human population resulting in consumption of resources over the replenishing rate, pollution of water sources, diseases spreading such as typhoid and cholera. The very main reason such occurrence is because of direct interaction of farming with nature. Farming is not a natural behaviour of an ecosystem (Despommier, 2009). It is a creation of human beings to increase its survival rate. Hence in a simple mathematical equation, if we remove farming from nature and put it in a closed system which resembles the nature ecosystem, we can remove the potential unsustainable acts of farming. The concept of vertical farming is to remove the factor of farming from nature to undo the bad deeds before it is too late. This simplistic solution might seem like a dreamer’s solution and appear to be impractical due to its high costs. To prove that argument disadvantages, this research will show the latest breakthrough in the agriculture industry in growing plants in a building while acquiring better results in agriculture end products. Thus, this research will be proposing to construct simplified miniature farm system that uses hydroponic system and govern by a system using the Hydroponic Monitoring Application (HMA)